Information Seeking Behaviour of Municipal Medical Center Visitors in Greece - Papavlassopoulos, Sozon; Ioannidou, Evdoxia; Kostagiolas, Petros; Stamou, Sofia; Poulos, Marios (Qualitative and Quantitative Methods in Libraries, 2019)
Context In the years of scarce economic resources the Municipal Health Centres (MHC) are becoming increasingly important for primary healthcare provision. The MHCs are close to the communities they serve, often cooperate with nongovernmental organizations and provide primary healthcare services often to vulnerable citizens originating from lower socio-economic backgrounds, unemployed people, immigrants, etc. Objective The paper deals with the information needs and information seeking preferences of MHC visitors. Our aim is to capture visitors’ information profile in order to propose healthcare information policies in order to improve equity, inclusiveness and fairness to vulnerable citizens. Methods A survey was conducted through a specially designed questionnaire distributed to visitors of the five major MHCs in Athens, Greece. Descriptive and inferential statistics as well as exploratory factor analysis has been carried out through SPSS (version 22). Results The information needs of visitors are related to prevention, diagnosis and prognosis. Healthcare professionals and the Internet are considered to be the main sources of information, while the individuals consider physician’s complicated language as the main information barrier. Conclusions Development of appropriate information services and advisory material for municipal health centres’ visitors based on their information seeking preferences may aid the healthcare system as a whole.